Molecular classification and genetic pathways in hyperplastic polyposis syndrome. - Carvajal-Carmona, L; Howarth, K; Lockett, M; Polanco-Echeverry, G; Volikos, E; Gorman, M; Barclay, E; Martin, L; Jones, A; Saunders, B; Guenther, T; Donaldson, A; et al. (2007)
Hyperplastic Polyposis (HPPS) is a poorly characterized syndrome that increases colorectal cancer (CRC) risk. We aimed to provide a molecular classification of HPPS. We obtained 282 tumours from 32 putative HPPS patients with >or= 10 hyperplastic polyps (HPs); some patients also had adenomas and CRCs. We found no good evidence of microsatellite instability (MSI) in our samples. The epithelium of HPs was monoclonal. Somatic BRAF mutations occurred in two-thirds of our patients' HPs, and KRAS2 mutations in 10%; both mutations were more common in younger cases. The respective mutation frequencies in a set of 'sporadic' HPs were 18% and 10%. Importantly, the putative HPPS patients generally fell into two readily defined groups, one set whose polyps had BRAF mutations, and another set whose polyps had KRAS2 mutations. The most plausible explanation for this observation is that there exist different forms of inherited predisposition to HPPS, and that these determine whether polyps follow a BRAF or KRAS2 pathway. Most adenomas and CRCs from our putative HPPS patients had 'classical' morphology and few of these lesions had BRAF or KRAS2 mutations. These findings suggest that tumourigenesis in HPPS does not necessarily follow the 'serrated' pathway. Although current definitions of HPPS are sub-optimal, we suggest that diagnosis could benefit from molecular analysis. Specifically, testing BRAF and KRAS2 mutations, and perhaps MSI, in multiple polyps could help to distinguish HPPS from sporadic HPs. We propose a specific model which would have diagnosed five more of our cases as HPPS compared with the WHO clinical criteria.